2015 IEEE International Conference on Industrial Technology (ICIT) 2015
DOI: 10.1109/icit.2015.7125517
|View full text |Cite
|
Sign up to set email alerts
|

MPPT algorithms comparison in PV systems: P&O, PI, neuro-fuzzy and backstepping controls

Abstract: This paper presents a comparative analysis of control methods to extract the maximum power and to track the maximum power point (MPP) from photovoltaic (PV) systems under changeable environmental conditions. The PV system consists of a solar module and a DC/DC converter, in this case a buck-boost converter, connected to a load. The maximum power point tracking (MPPT) algorithms compared are the perturb and observe (P&O) method, the PI control, a neuro-fuzzy and fuzzy technique and finally a backstepping contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…R. Vazquez, [6]. Being a robust non-linear controller, Lyapunov functions also guarantees the system stability along with reaching its control objective, to track optimum power under variable atmospheric conditions.…”
Section: Backstepping Control Strategymentioning
confidence: 99%
“…R. Vazquez, [6]. Being a robust non-linear controller, Lyapunov functions also guarantees the system stability along with reaching its control objective, to track optimum power under variable atmospheric conditions.…”
Section: Backstepping Control Strategymentioning
confidence: 99%
“…The main objective of the first stage (boost converter) is allowing the PV array to generate the maximum power using the MPPT technique [9]. There are several algorithms used to track the MPP effectively; the authors of [10] showed that the back-stepping algorithm gives good results. Several publications explore two broad categories of MPPT techniques: indirect MPP tracking like the fractional open circuit voltage method [11], direct MPP tracking like the incremental conductance [12,13], or the Perturb and Observe (P&O) method that is implemented in this work.…”
Section: Introductionmentioning
confidence: 99%
“…In [14], the rise time of the back-stepping control of MPPT and the integral back-stepping were 2.42 ms and 2.17 ms, respectively. In [10], efficiencies of 96%, 96.5%, 98.2%, and 99.1% were obtained by using P&O algorithm, PI, neuro-fuzzy, and back-stepping, respectively. Our main objectives are to achieve a lower response time and higher efficiency in the MPPT stage.…”
Section: Introductionmentioning
confidence: 99%
“…To address these issues, the non-linear commands, such as the backstepping [6] and the sliding mode [7], and the artificial intelligence controls, such as the Artificial Neural Network (ANN) [8] and the fuzzy logic [9], have been designed. Indeed, despite of the implementation complexity of these techniques, they have better performance criteria [10,11].…”
Section: Introductionmentioning
confidence: 99%